(untitled) (Bulletin of criminological association of Ukraine, 2025)
The scientific article is devoted to the analysis of quantitative indicators of criminal separatism. It is emphasized that the level of criminal separatism is considered through the prism of the analysis of the level of crimes, the level of criminals and the level of convictions. At the same time, for a more effective analysis, the level of crime should be analyzed using crime coefficients. It is noted that one of the main quantitative indicators of crime is the dynamics of crime. At the same time, the main indicators of the dynamics of crime are the following: absolute growth (decrease), growth rate (decrease) and growth rate (decrease). In conclusion, it is emphasized that quantitative indicators of crime make it possible to formulate a criminological view of criminal separatism from the point of view of quantitative measurement.